“THE RELATIONSHIP BETWEEN ARM MUSCLE STRENGTH, BACK MUSCLE STRENGTH, LEG MUSCLE STRENGTH, AND HAND-EYE COORDINATION WITH THE OVERHEAD VOLLEYBALL SERVING ABILITY OF MALE STUDENTS AT SMP 12 BENGKULU CITY”: “THE RELATIONSHIP BETWEEN ARM MUSCLE STRENGTH, BACK MUSCLE STRENGTH, LEG MUSCLE STRENGTH, AND HAND-EYE COORDINATION WITH THE OVERHEAD VOLLEYBALL SERVING ABILITY OF MALE STUDENTS AT SMP 12 BENGKULU CITY” - Dwingki, Dwingki Marta Putra (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
In performing a volleyball serve, arm muscle strength, back muscle strength, leg muscle strength, and hand–eye coordination make a fairly dominant contribution. Therefore, this study aims to determine the relationship between arm muscle strength, back muscle strength, leg muscle strength, and hand–eye coordination with the overhand serving ability of male students at junior high school 12 bengkulu city. this research is correlational and uses a survey method with test and measurement instruments. the subjects of the study were 16 male students of junior high school 12 bengkulu city. the data analysis technique used regression analysis at a 5% significance level. based on the results of the study, the first hypothesis test obtained a calculated r value of 0.770 > r table (0.05)(15) = 0.412. the second hypothesis test obtained a calculated r value of 0.698 > r table (0.05)(15) = 0.412. the third hypothesis test obtained a calculated r value of 0.784 > r table (0.05)(15) = 0.412. the fourth hypothesis test obtained a calculated r value of 0.809 > r table (0.05)(15) = 0.412. the fifth hypothesis test obtained a calculated f value of 17.443 > f table (3.36). it can be concluded that there is a significant relationship between arm muscle strength, back muscle strength, leg muscle strength, and hand–eye coordination with the overhand volleyball serving ability of male students at junior high school 12 bengkulu city.